OPTIMIZATION OF DRYING PROCESS OF CORN NOODLES USING FLUIDIZED BED DRYER - TJAHJA MUHANDRI; SUBARNA; AFIFAH ZAHRA AGISTA; PURWIYATNO HARIYADI; AMINULLAH (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Drying process was one of the main factors in preserving noodles because it can reduce water content to less than 12 % (w/w (weight by weight)). The objectives of this study were to optimize the drying process of corn noodles using fluidized bed dryer (temperatures of 50 °C, 60 °C, and 70 °C with airflow velocities of 0.73 m‧s-1, 1.53 m‧s-1, and 2.17 m‧s-1) and to determine the influence of water addition (60 %, 70 %, and 80 % (w/w)) to the dough of corn noodles. The results showed that the best rehydration profile of dried noodles was obtained from drying process at temperature of 60 °C with airflow velocity of 2.17 m‧s-1. The quality of dried corn noodles was influenced by final moisture content of dried noodles and water addition. The critical moisture contents on water additions of 60 %, 70 %, and 80 % were 12, 11, and 10 % (w/w), respectively. The results also showed the optimum quality of dried corn noodles which was obtained from the dough with water addition of 80 %, drying temperature of 60 °C with velocity of 2.17 m‧s-1 for 107 minutes, and moisture content of 10 %. This has similar properties of moisture content, cooking loss, elongation, and hardness to the conventional drying.